Aligning Who I Am with What I Do: Pursuing Language Teacher Authenticity - Gregersen, Tammy (Theory and Practice of Second Language Acquisition, 2015)
This study explores the dynamic, interactive relationship between teacher identity and authenticity. Through an examination of several socio-cultural (social identity, situated learning, and image text) and psycholinguistic (individual differences) second language acquisition theories, a conceptualization of identity is provided. Subsequently, language teacher authenticity is characterized from both a philosophical and pedagogical perspective and connected to the notion of teacher identity. The final section of the paper presents research-based applications that include reflecting critically, redefining personal credibility, discovering one’s personal style, displaying emotion and recognizing diversity to facilitate the positive-broadening quest of aligning one’s identity (i.e., who I am) with authenticity (i.e., what I do).